Communication rehabilitation in sub-Saharan Africa: A workforce profile of speech and language therapists - Wylie, Karen; McAllister, Lindy; Davidson, Bronwyn; Marshall, Julie (AOSIS, 2016)
Background There is an urgent global need to strengthen rehabilitation services for people with disabilities. In sub-Saharan Africa, rehabilitation services for people with communication disabilities continue to be underdeveloped. A first step in strengthening services for people with a communication disabilities is to understand the composition and conditions of the current workforce.